Sovereign Default and Imperfect Tax Enforcement - Francesco Pappadà; Yanos Zylberberg (Center for Economic Studies and ifo Institute (CESifo), 2019)
We show that, in many countries, tax compliance is volatile and markedly responds to fiscal policy. To explore the consequence of this novel stylized fact, we build a model of sovereign debt with limited commitment and imperfect tax enforcement. Fiscal policy persistently affects the size of the informal economy, which impact future fiscal revenues and thus default risk. This mechanism captures one key empirical regularity of economies with imperfect tax enforcement: the low sensitivity of debt price to fiscal consolidations. The interaction of imperfect tax enforcement and limited commitment strongly constrains the dynamics of optimal fiscal policy. During default crises, high tax distortions force the government towards extreme fiscal policies, notably including costly austerity spells.
Keywords: E02; E32; E62; F41; H20; 330; sovereign default; imperfect tax enforcement; informal economy; fiscal policy